Training Load and Current Soreness Predict Future Delayed Onset Muscle Soreness in Collegiate Female Soccer Athletes - Brett S. Pexa; Christopher J. Johnston; Jeffrey B Taylor; Kevin R. Ford (International Journal of Sports Physical Therapy)
# Background